ANALISA DAMPAK PROMOSI DAN SANKSI PADA KECURANGAN PAJAK USAHA KECIL DAN MENENGAH DI KOTA DENPASAR - I Gusti Ngurah Putra Harthawan; I Komang Arnata (KRISNA: Kumpulan Riset Akuntansi, 2026)
Small and Medium Enterprises (SMEs) are businesses that continue to grow with good resilience to macroeconomic turmoil. The large number of units with relative income has made them potential tax objects. The reality in the field shows that not all SMEs have the compliance to complete their tax obligations. This study aims to determine the effect of tax promotion and tax sanctions on taxpayer compliance who are SMEs in Denpasar City. The number of samples used was 100 people and the multiple regression test method has produced a conclusion. Tax promotion and tax sanctions have a positive and significant effect on taxpayer compliance. The results show the need for better and more massive tax promotion efforts to improve taxpayer compliance. Firmness in implementing tax sanctions also needs to be increased to improve taxpayer compliance.